PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN BALARAJA - Evalin Ndoen; Alberth Supriyanto Manurung (Sekolah Tinggi Pariwisata Mataram, 2021)
The purpose of this study was to identify: 1) principal’s leadership at SD Negeri Kecamatan Balaraja, 2) teacher’s performance at SD Negeri Kecamatan Balaraja, and 3) the influence of principal leadership towards teacher’s performance at SD Negeri Kecamatan Balaraja. This study uses quantitative approach, non-experiment model with correlational design. Subject of this research are principal and teacher of elementary public school in Kecamatan Balaraja. Instrument of this study is questionnaire. The result of this study based on descriptive analysis shows that both variables which are principal leadership and teacher performance is in middle category with percentage 53,75 % for principal leadership and 71,42 % for teacher’s performance. Whereas hypothetically, the result of the study is there is a middle correlation for principal leadership and teacher’s performance with value 0,457 and based on the result there is significant influence of principal leadership towards teacher performance with coefficition determination value is 0,299 (29,9 %) which indicates that predictive ability of independent variable (principal leadership) to dependent variable (teacher performance) in this research is 29,9. According to the results, the conclusion is there is significant influence of principal leadership towards teacher performance.